Factors associated with and impact of burnout in nursing and residential home care workers for the elderly - Harrad, Rachel; Sulla, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Numbers of elderly people worldwide continue to grow. Increasingly these individuals require nursing and residential care to meet their needs. Nursing is an occupation associated with burnout amongst its workforce, associated with increases of emotional exhaustion, depersonalisation and decreases in personal accomplishment. This review of literature provides a more detailed picture of the associations and predictors of burnout within this setting, and also considers the implications this holds for patient care, before providing recommendations for managers of such settings. Methods: Literature searches were conducted across a range of academic databases with a series of relevant keywords. Results: Examination of search results suggested several factors relating to staff burnout including occupational aspects, types of setting, staff perceptions, coping strategies, education and training and the impact of burnout on care delivery. Conclusions: Studies from across the globe suggest that burnout is prevalent amongst staff working in nursing and residential homes caring for elderly people, with implications for the patients, staff and homecare providers. Factors associated with burnout appear to include perceptions of job stress and occupational aspects, as well as the types of coping mechanisms staff employ. Managing grief associated with death of patients at work, as well as staff perceptions of both clients and their illnesses also appear related to burnout as well as the specific type of healthcare setting.